2016
DOI: 10.18203/2394-6040.ijcmph20161371
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of prevalence of protein energy malnutrition in under 5 year children in an urban slum of Mumbai, India and to study associated factors

Abstract: INTRODUCTIONEach type of malnutrition is the result of a complex interplay of factors involving such diverse elements as household access to food, maternal and child-care, safe water and sanitation and access to basic health services. Children, who fail to get enough medical attention or receive only fragmented care, grow up shattered, both in body and mind. These children are to become our next generation. We will be left with a legacy of damaged ABSTRACT Background: In urban slums, several socio-demographic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
3
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 2 publications
(2 reference statements)
5
3
0
Order By: Relevance
“…6,7 ARI episodes in past 6 months was observed significantly among one-fifth of underweight children and diarrhoea episodes in past 6 months among nearly one-third underweight children that shown similar finding reported by Tiwari et al study. 4 Incomplete immunizations were detected among nearly two-fifth of underweight children which shown similar findings by Gondikar et al, Shukla et al and opposite findings by Tiwari et al study. 4,5,7 Rafath et al study as compared to similar finding observed for handwashing practices of mother and comparatively less proportion observed for always use soap for hand wash by mother in the present study.…”
Section: Resultssupporting
confidence: 69%
See 2 more Smart Citations
“…6,7 ARI episodes in past 6 months was observed significantly among one-fifth of underweight children and diarrhoea episodes in past 6 months among nearly one-third underweight children that shown similar finding reported by Tiwari et al study. 4 Incomplete immunizations were detected among nearly two-fifth of underweight children which shown similar findings by Gondikar et al, Shukla et al and opposite findings by Tiwari et al study. 4,5,7 Rafath et al study as compared to similar finding observed for handwashing practices of mother and comparatively less proportion observed for always use soap for hand wash by mother in the present study.…”
Section: Resultssupporting
confidence: 69%
“…4 Incomplete immunizations were detected among nearly two-fifth of underweight children which shown similar findings by Gondikar et al, Shukla et al and opposite findings by Tiwari et al study. 4,5,7 Rafath et al study as compared to similar finding observed for handwashing practices of mother and comparatively less proportion observed for always use soap for hand wash by mother in the present study. 8 Untrimmed nails were detected among one-third of underweight children and distance of located PHC >5 km was placed among three-fifth of underweight children highly significant which shows similar result reported by Biswas et al that distance of a health center affect health status.…”
Section: Resultssupporting
confidence: 69%
See 1 more Smart Citation
“…A study conducted by Tiwari et al among under five children of urban slum of Mumbai found significant association between birth order of child and malnutrition. 16 Women's age at marriage and child malnutrition was also statistically significant (p=0.009). Raj et al concluded that the risk of malnutrition is higher among young children born to mothers married as minors than in those born to women married at a majority age.…”
Section: Discussionmentioning
confidence: 94%
“…Mother's educational status was significantly associated with under-nutrition in the study done at Kalaburagi District of Karnataka [25]. Various studies done by Tiwari SR et al [33] in Mumbai, Sarkar S et al [34] in West Bengal and Upadhyay et al [35] in Puducherry showed that household income was significantly associated with malnutrition.…”
Section: Original Research Articlementioning
confidence: 99%